SMART-Based Feedback Guidelines to Improve Student Learning Motivation and Self-Efficacy - Ni Made Viona Adelia Cahyani; I Wayan Widiana; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2024)
This research was triggered by a lack of understanding of teachers in providing effective feedback in elementary schools, which is often delivered simply without in-depth explanations. This study aims to develop guidelines for providing SMART-based feedback (Specific, Measurable, Achievable, Relevant, and Time-bound). In addition, this study also includes an analysis of the validity of media content, evaluation of teachers' responses to the media, and an assessment of its effectiveness on learning motivation and self-efficacy of elementary school students. This study adopts a 4D model with the subject of SMART-based feedback guidelines, and the object of this research includes the validity of the content, language, design, as well as user reactions and the effectiveness of the media. The data collection method involves conducting interviews, observations, and using questionnaires/questionnaires using rating scale and questionnaire instruments. With the availability of SMART-based feedback guidelines, teachers have a clear reference in providing more structured and effective feedback. These guidelines not only help increase students' motivation to learn, but also encourage them to achieve real, measurable, and continuous improvements in the learning process, so that learning outcomes can be more optimal. The results of the study show that the feedback guidelines developed have a high level of content validity, receive very good responses from teachers, and are significantly effective in increasing students' learning motivation and self-efficacy. Thus, this guideline is considered feasible, practical, and effective to be used in providing feedback in elementary schools.